Concentración de plomo en agua y sedimentos en el humedal La Segua, provincia de Manabí - Córdova Dávila, Marco Antonio (2020)
The present investigation evaluates the incidence of the productive activities in the concentration of lead (Pb) in water and sediments present in La Segua wetland, by means of a diagnosis of the productive activities around the wetland, two activities that directly influence the lead contamination are (aquaculture and agricultural activity); five sampling points were established, located at strategic points in the body of water, next to productive activities; once the results of the laboratory were obtained, the presence of Lead in water and sediment at various sampling points (PM) was determined and compared with current environmental legislation (TULSMA, RO N ° 387), instead the specific results of the sediment sample were compared with international environmental regulations (Canadian Council of Ministers of the Environment) with the sediment quality criterion for the protection of aquatic life in estuaries. According to the results, the concentration of Pb in water in December at sampling points B and C was 0.012 mg / l, a value that is above the maximum permissible limit of national legislation; on the other hand, the results of Pb in sediment registered the highest concentration at the sampling point C in October, with 1,736 mg / Kg /; the lowest was recorded at sampling point B in December, with 0.272 mg / Kg, confirming that the values are below the permitted level of Canadian regulations.